A randomized controlled trial of a web-based mindfulness programme for people with MS with and without a history of recurrent depression. (August 2022) - Sesel, Amy-Lee; Sharpe, Louise; Beadnall, Heidi N; Barnett, Michael H; Szabo, Marianna; Naismith, Sharon L
Background: Evidence shows small positive effects associated with psychological treatments for people with multiple sclerosis (PwMS). In a recent meta-analysis, the treatment with the largest effect size was a mindfulness-based intervention (MBI). Objectives: We aimed to determine whether an Internet-delivered MBI was beneficial for PwMS. Furthermore, we aimed to investigate history of recurrent depression as a moderator of treatment outcome. Methods: Participants ( N  = 132) were assessed based on whether they had a history of recurrent depression, then stratified and randomized to MBI or waitlist. Outcomes were assessed at baseline, post-intervention, and 3 and 6 months. Results: The MBI group reported significantly improved depressive symptoms (primary outcome) compared with the waitlist ( p  = 0.046, Cohen's d  = 0.39). Those with a history of recurrent depression benefitted significantly more than those without ( p  = 0.034, d  = 0.66). There were benefits for health-related quality of life (HRQoL) in the MBI, irrespective of depression history ( p  = 0.009, d  = 0.5). Pain interference was less overall in the MBI group ( p  < 0.001, d  = 0.2), but change over time did not differ from waitlist. There were no treatment effects for anxiety, pain severity or fatigue. Conclusion: The Internet-delivered MBI significantly improved depressive symptoms and HRQoL in PwMS. For depression, the benefits were greater for those with a history of recurrent depression. Trial Registration: ACTRN12618001260213, available at:https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=375598